Faktor-faktor Yang Berhubungan Dengan Praktik Wanita Pekerja Seks (WPS) dalam VCT Ulang di Lokalisasi Sunan Kuning Kota Semarang - Widiyanto, Gunawan; Widjanarko, Bagoes; Suryoputro, Antono (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2009)
Background: Female Sex Workers (FSWs) is one of the high risk groups of HIV and other Sexual Transmitted Infections. They are engaged in unsafe sex practices with multi partner. Therefore, they should conduct HIV test regularly to prevent them from HIV transmission. This study aims to analyze the factors associated with FSWs’ VCT repeat practices at SunanKuning Brothel.Method: It was a cross sectional study, involved 90 FSWs from total 635 populations.Result: Based on 95% confidence interval and 50% assumed proportion, it was found 71.1% of FSWs had a good belief about VCT and 75.6% had a good value of knowing their HIV status. Most of them (97.8%) were having good support to be re-tested and 86.7% complied with others’ support. The vast majority of FSWs (88.9%) perceived the VCT clinic was wellorganized, only few of them did not satisfy with VCT clinic’s service.Bivariate analysis employed chi-square test showed that belief on VCT (p=0.000), value of knowing their HIV status (p=0.000) and motivation to comply other’s support (p=0.000) were significantly associated with FSWs’ VCT repeat practices. Multivariate analysis found that belief about VCT contributed more than other variables in predicting FSWs’ VCT repeatpractices.Keywords : Female Sex Worker, VCT Repeat Practice, Sunan Kuning